Encyclopedia of Industrial Biotechnology 2010
DOI: 10.1002/9780470054581.eib467
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Transfer Rate Determination: Chemical, Physical and Biological Methods

Abstract: A proper mechanical design of the bioreactor is aimed at maintaining the environmental and nutritional conditions for optimal growth and/or product formation. Among the various environmental and nutritional factors that influence the aerobic bioprocess, oxygen is a critical parameter since it is the only nutrient that has to be provided continuously, even in batch cultures. The oxygen transfer rate (OTR) determination is essential in order to establish aeration efficiency and to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…For OTR characterisation, kLa values were determined at different volumetric air flow rates and power inputs according to the physical dynamic method . Accordingly, the change in dissolved oxygen (DO) was monitored after switching the feed gas from nitrogen to air.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For OTR characterisation, kLa values were determined at different volumetric air flow rates and power inputs according to the physical dynamic method . Accordingly, the change in dissolved oxygen (DO) was monitored after switching the feed gas from nitrogen to air.…”
Section: Methodsmentioning
confidence: 99%
“…These findings were unexpected as the fermentations in both reactors were carried out at analogous k L a conditions. It has previously been reported that the physical dynamic method yields lower k L a values than methods that measure oxygen consumption [28] due to back mixing of bubbles with elevated nitrogen content [20]. This effect may be more prominent in an ELR as fine bubbles with elevated nitrogen content can remain in the reactor longer.…”
Section: Batch Fermentationsmentioning
confidence: 99%
“…When sparging is used for aeration, the oxygen transfer rate is defined as the amount of oxygen transferred from the gas into the liquid phase, where it is taken up by the microbes (oxygen uptake rate) [46]. This oxygen transport can be described by several mass transfer resistances, which decrease the final oxygen attained relative to the amount of oxygen supplied.…”
Section: Oxygen Dosing Techniquesmentioning
confidence: 99%
“…Physical methods for k L a estimation are based on dissolved oxygen (DO) concentration changes with time, where dynamic gassing‐in and gassing‐out procedures are still the most commonly used . However, these approaches could become inaccurate if the delay of the measuring system is neglected .…”
Section: Introductionmentioning
confidence: 99%
“…10 Physical methods for k L a estimation are based on dissolved oxygen (DO) concentration changes with time, 2,10 where dynamic gassing-in and gassing-out procedures are still the most commonly used. 1,11,12 However, these approaches could become inaccurate if the delay of the measuring system is neglected. 2,13 -15 This can mainly be attributed to the response time , e , of the electrode's probe, whose dynamic response can be approximated by the following first-order equation: 2,11,14,16…”
Section: Introductionmentioning
confidence: 99%